2010
DOI: 10.1186/1476-511x-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of vinegar intake on some biochemical risk factors of atherosclerosis in hypercholesterolemic rabbits

Abstract: BackgroundExaggerated postprandial spikes in blood glucose and lipids induce proportional increases in oxidative stress, which acutely trigger impairment endothelial, inflammation and increased risk of future cardiovascular events. In this research, we have investigated acute effects of vinegar intake on some of the biochemical atherosclerosis risk factors in high cholesterol fed rabbits to see if we can find a probable protective value for it.MethodsThe rabbits were randomly divided into four groups: normal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 77 publications
(42 reference statements)
3
60
1
2
Order By: Relevance
“…Dr. James Lind in 1746 compared vinegar, dilute sulfuric acid, cider, sea water, a physician's remedy of nutmeg, garlic and horseradish mixture versus a diet of oranges and lemons to prevent scurvy [28]. Recent data in animals suggest vinegar improves lipids, and our small non randomized trial implied improvement in HDL-C [21][22][23]. Unfortunately, our larger randomized trial results did not indicate that apple cider vinegar impacted HDL-C compared to control.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Dr. James Lind in 1746 compared vinegar, dilute sulfuric acid, cider, sea water, a physician's remedy of nutmeg, garlic and horseradish mixture versus a diet of oranges and lemons to prevent scurvy [28]. Recent data in animals suggest vinegar improves lipids, and our small non randomized trial implied improvement in HDL-C [21][22][23]. Unfortunately, our larger randomized trial results did not indicate that apple cider vinegar impacted HDL-C compared to control.…”
Section: Discussioncontrasting
confidence: 41%
“…The dietary intake of vinegar has been reported to lower triglyceride levels [21], reduce LDL-C, and raise HDL-C in several animal studies [22,23]. We performed a small nonrandomized pilot study with one, two, three or six teaspoons of apple cider vinegar and found an increase in HDL-C trended with increase in dose.…”
Section: Introductionmentioning
confidence: 99%
“…Kao novi svetski trend nameće se prevencija ovih obolenja uvođenjem u ishranu prirodnih antioksidanasa. Mirođija je zbog svoje aromatičnosti jedan od omiljenih suplemenata, a dokazano je i da deluje preventivno na navedene bolesti (Yazdanparast andBahramikia 2008, Sahib et al 2012, Thukham-Mee and Wattanathorn 2012, Setorki et al 2013, Mishra 2013). Etarsko ulje plodova mirođije može da se koristi za kontrolu skladišnih insekata, bubašvaba i muva (Babri et al 2012, Khani and.…”
Section: Etarskom Ulju Mirođije Identifikovano Je 15 Komponenti a Dounclassified
“…The method used is a modification of Setorki et al (2010). Baseline blood samples were drawn from the tail of the rats before they were given treatments.…”
Section: Assay and Measurement Of Biochemical Factors In Rattus Albusmentioning
confidence: 99%